The Effect Of Flash Sales And Free Shipping On Purchase Decisions Among E-Commerce Users - Susanti, Reza Septi; Wijaya , Ermi; Herlin, Herlin (Utami Publisher, 2025)
The purpose of this study is to test whether there is an influence between flash sale and free shipping on purchasing decisions in e-commerce users. This research focuses on Tiktok Shop e-commerce. Based on the characteristics of the research, a sample of 100 respondents was obtained and the research analysis used multiple linear regression analysis. The research results show that the influence of flash sale (X1) on purchasing decisions in e-commerce users (Y) based on the results of the thitung test for the free shipping variable (X2) is 3,423 the thitung value if compared to the ttabel of 1,660 and thitung>ttable (3,423>1,660) with a significance level of 0.001<5% then Ho is rejected and Ha is accepted. The existence of the effect of free shipping (X2) on the purchase decision of e-commerce users (Y) based on the results of the count test for the free shipping variable (X2) is 2,789, the value of the value if compared to the table of 1.660 and the table> table (2,789>1.660) with a significance level of 0.003<5% then Ha is rejected and Ho is accepted. The simultaneous influence of flash sale (X1) and free shipping (X2) on the purchase decision of e-commerce users (Y) based on the Ftable result of 3.06 because Fcalculate>Ftable (15,787>3.06) then Ha is accepted and Ho is rejected, which means that there is a significant effect of the flash sale variable (X1), free shipping (X2) together or simultaneously on the purchase decision on e-commerce users (Y). Multiple linear regression results have the equation Y= 21,918+ 0,448 X1 + 0,196X2 +e because of the positive regression direction, it can be interpreted that if Flash sale and free shipping increase, then the purchase decision of e-commerce users will also increase. The value of the coefficient is terminated Adjusted R Square R2= 0,800. This value means that independent variables together contribute 80.% in influencing dependent variables with medium criteria.